A novel scoring system to predict the outcomes of adult patients with hypoxic-ischemic encephalopathy. (3rd April 2018) - Li, Feng; Liu, Guangwei; Tian, Xin; Quan, Fengying; Li, Bosong; Feng, Guibo; Wang, Xuefeng; Hu, Yida
ABSTRACT: Background: Adult patients with hypoxic-ischemic encephalopathy (HIE) often incur large costs, but their outcomes are poor. Currently, there is lack of a comprehensive quantitative approach to predict patient prognoses. Methods : A total of 73 adult patients with HIE participated in this prospective, observational study. Clinical assessments, laboratory tests, and electrophysiological examinations were conducted within 3 days after HIE occurred. Logistic regression model was used to identify independent factors associated with patient outcomes. Results : After a 6-month follow-up, 44 (61.1%) patients survived, 28 (38.9%) patients died, and one patient was lost to follow-up. The level of blood calcium and lactate, the presence of electroencephalography reactivity, and Glasgow Coma Scale (GCS) score were significantly associated with the patient's outcome. Based on the regression coefficients from logistic regression analysis, we constructed a scoring system (CEGL; C: calcium, E: EEG reactivity, G: GCS, L: lactate) to predict the possibility of a patient's death. The area under the receiver operating characteristic curve was 0.91 (P < 0.001, 95% CI [0.87–0.95]) with a specificity of 97.7% and a positive predictive value of 97.4%. Conclusion: CEGL score can provide clinicians useful information for assessment of patient prognosis within 6 months after HIE.